2012
DOI: 10.1177/0961203312436863
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about self-reported fatigue in systemic lupus erythematosus?

Abstract: Fatigue is one of the most complex and ill understood symptoms of chronic illness often reported as the number one complaint by patients with systemic lupus erythematosus (SLE). This paper aims to provide a comprehensive review of the literature on fatigue in SLE. A pool of 55 relevant articles was retrieved via electronic searches of six databases including MEDLINE, EMBASE, CINAHL, AMED, PsychINFO and PubMed. Fatigue in the studies reviewed was assessed by a range of self-report instruments, the content of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 65 publications
(197 reference statements)
3
57
0
3
Order By: Relevance
“…Fatigue improved by an approximate average of 4 points (post-intervention) and 3 points (four months post-intervention) in intervention participants, which is greater than the minimum clinically significant change suggested for interpreting change scores in lupus trials[4647]. It is notable that while the mean fatigue score for intervention participants decreased post-intervention, the mean fatigue score for control participants actually increased.…”
Section: Discussionmentioning
confidence: 81%
“…Fatigue improved by an approximate average of 4 points (post-intervention) and 3 points (four months post-intervention) in intervention participants, which is greater than the minimum clinically significant change suggested for interpreting change scores in lupus trials[4647]. It is notable that while the mean fatigue score for intervention participants decreased post-intervention, the mean fatigue score for control participants actually increased.…”
Section: Discussionmentioning
confidence: 81%
“…Fatigue accompanies inflammation and is frequently reported among patients with a wide range of chronic inflammatory conditions. The prevalence of fatigue in patients with RA, defined as a score of > 20 on the fatigue visual analogue scale, was reported to be 41% in one study, and fatigue is among the most commonly reported phenomena in multiple sclerosis, pSS and SLE . In inflammatory diseases, as well as in cancer‐related fatigue, the fatigue has sometimes been related to altered or increased proinflammatory cytokine production .…”
Section: Fatigue In Chronic Diseasesmentioning
confidence: 99%
“…The prevalence of fatigue in patients with RA, defined as a score of > 20 on the fatigue visual analogue scale, was reported to be 41% in one study, 66 and fatigue is among the most commonly reported phenomena in multiple sclerosis, pSS and SLE. [67][68][69][70] In inflammatory diseases, as well as in cancer-related fatigue, the fatigue has sometimes been related to altered or increased proinflammatory cytokine production. 71,72 However, in general there seems to be a poor correlation between disease activity and the severity of fatigue.…”
Section: Fatigue In Chronic Diseasesmentioning
confidence: 99%
“…25 It is not included in the ACR criteria but it can significantly affect behavior and function, 26 is extremely common in SLE, and often does not respond to traditional SLE treatments. 27 In this respect, quality-of-life questionnaires usually include fatigue, so although they should not replace more comprehensive neurologic and psychological instruments, they are useful to include in the diagnostic repertoire.…”
Section: Symptoms Of Npslementioning
confidence: 99%